Guide to methods for students of political science - Van Evera, Stephen (Cornell University Press, 1997)
Stephen Van Evera greeted new graduate students at MIT with a commonsense introduction to qualitative methods in the social sciences. His helpful hints, always warmly received, grew from a handful of memos to an underground classic primer. That primer evolved into a book of how-to information about graduate study, which is essential reading for graduate students and undergraduates in political science, sociology, anthropology, economics, and history - and for their advisers.